PENGARUH LITERASI EKONOMI DAN KONTROL DIRI TERHADAP PENGELOLAAN KEUANGAN KELUARGA (STUDI KASUS IBU RUMAH TANGGA DI DESA LAIYOLO BARU) - Inanna, Inanna; Nesvita, Erma; Nurdiana, Nurdiana; Supatminingsih, Tuti; Hasan, Muhammad (Politeknik Negeri Lhokseumawe, 2023)
The purpose of this study was to determine the effect of economic literacy and self-regulation on family financial management in Laiyolo Baru Village. This research uses a type of quantitative research with a descriptive approach. Questionnaires and documentation are used as data collection methods. The population in the study were 53 housewives. The data analysis technique used is the classical assumption test, multiple linear regression analysis, f test, t test and the coefficient of determination. The results showed that the variables of economic literacy (X1) and self-control (X2) had an effect on the financial management of housewives in Laiyolo Baru Village.Keywords : Economic Literacy, Self-Control, Financial Managemen.